Formulation of Econazole Nitrate as an Ophthalmic Ointment - Fatohy, Heba Antwan (Zanco Journal of Medical Sciences (ZJMS), 2009)
Background and objective: Keratomycosis is an important cause of ocular morbidity and can lead to blindness due to lack of ocular antifungal agents. The goal of this study is to formulate a stable effective formula of econazole nitrate ophthalmic ointment.Econazole nitrate has an advantage over other antifungal agents in treatment of mixed infection since it is active against both dermatophytes and candida, and also it is effective in the treatment offilamentous fungi. Methods: Econazole nitrate ophthalmic ointment of different strength were formulated and compared for their in vitro activity.The effect of different factors (light and type of container) and calculating the expiration date of the selected formula were studied. Results: Formula A (1gm Econazole nitrate in 100 gm ophthalmic ointment base) and formula B (2gm Econazole nitrate in 100gm ophthalmic ointment base) had good in vitro antifungal activity because both formula A and B inhibit the growth of the fungi used, but formula A was selected because it has the lowest concentration and the same activity. Also the results indicated that the selected formula A was affected by light and its % remaining was (96.7%), while there was no effect of the type of container used to store Econazole nitrate ophthalmic ointment.The expiration date of formula A was calculated to be (2.19) years. Conclusion: 1% Econazole nitrate ophthalmic ointment appears to be effective in vitro and should be stored in dark container .